An unusual case of orthodeoxia. Issue 6 (December 2021) - Khan, M. Zuabair; Figueredo, Vincent; Gandhi, Nisha; Kutalek, Steven; Kilcoyne, James
Abstract: Progressive hypoxia in hospitalized patients can be due to many etiologies, especially in patients with multiple comorbidities. More unusual causes of hypoxia, such as patent foramen ovale (PFO) with a right to left shunting in the absence of elevated right atrial pressures, should be considered when workup does not reveal a specific etiology. <Learning objectives: Hypoxemia due to a right-to-left atrial shunt with normal pulmonary arterial pressures can be seen in the aortic aneurysm patients.>